Optimization of biosurfactant production for enhanced crude-oil degradation by a Candida tropicalis 1214-BK14 isolated from white tiger oilfiel - Vung Tau, Vietnam - Hoa, Kiều Thị Quỳnh; Yên, Nguyễn Thị; Yến, Đặng Thị (Vietnam Journal of Biotechnology, 2018)
Biosurfactants are amphiphilic molecules with effective surface-active and biological properties applicable to replace synthetic surfactant in petroleum industry. Interest in microbial surfactants has been steadily increasing in recent years, as they have numerous advantages compared to chemical surfactants including a lower toxicity, better environmental compatibility and effective properties at extreme temperature, pH levels and salinity. A crude oil-degrading yeast strain (C. 1214-BK14) was selected among the isolated strains as a potential biosurfactant-producer from producing oil wells at White Tiger oilfield because of its ability to produce biosurfactant using crude oil as a sole carbon source. An emulsification index (E24%) of 57% was obtained initially by Candida tropicalis 1214-BK14 in previous study. Therefore, the optimization of biosurfactant production of this strain for enhanced crude oil degradation was carried out based on central composite design and analyzed using response surface methodology (RSM). The biosurfactant production process was investigated as function of three independent variables: crude oil (2.5-5 % w/v), (NH4)2SO4 (0.35-0.45% w/v), and solution pH (5-8). RSM analysis showed that the optimum condition for the biosurfactant production by C. tropicalis 1214-BK14 were 6.1, 3.97% (w/v) and 0.37% (w/v) for pH, concentration of carbon (crude oil) and nitrogen substrate ((NH4)2SO4), respectively, with the emulsification index measured in the conditions was 80.2%. The total crude oil and C10-C43 alkanes degradation efficiency by this strain estimated using GC/MS were 89.8% and 80.47-98.58%, respectively. These results revealed that the strain Candida tropicalis 1214-BK14 exhibited a tremendous potential for contaminated-crude oil degradation and microbial enhanced oil recovery (MEOR).